Modified polypropylene plastic added with glass fibers and preparation method of modified polypropylene plastic

By using multi-layer structure toughening agent, modified sepiolite/nitrogen-phosphorus composite flame retardant and g-alumina nanofiber to coat glass fibers in polypropylene materials, the insufficient impact performance of polypropylene materials at low temperatures is solved. The problem of this paper improves the flame retardancy and water resistance of the material, and meets the performance requirements of the battery cover of the new energy vehicle.

CN119264563AInactive Publication Date: 2025-01-07得彩新材料(山东)有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411666531.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polypropylene materials lack impact performance at low temperatures, and the flame retardancy and water resistance are difficult to meet the needs of the battery cover of new energy vehicles.

Method used

The core-shell toughening agent with octamethylsilsesquioxane as the core and polyacrylate as the shell is prepared by chemical bonding of core-shell emulsion with butadiene rubber as the core and polyacrylate as the shell is prepared by preparing toughening The agent, combined with modified sepiolite/nitrogen-phosphorus composite flame retardant and short-clad glass fibers coated with g-alumina nanofiber, forms a multi-layer structure to improve the mechanical properties and flame retardant properties of the material.

Benefits of technology

The excellent impact performance of modified polypropylene plastic at room temperature and low temperature is achieved, the flame retardant performance and water resistance are improved, and the mechanical properties and flame retardant performance of the material are balanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of modified polypropylene plastics, and particularly relates to a modified polypropylene plastic added with glass fibers and a preparation method of the modified polypropylene plastic. The modified polypropylene plastic added with the glass fibers is prepared from the following raw materials in parts by mass: 50 to 70 parts of polypropylene, 15 to 25 parts of modified sepiolite / nitrogen-phosphorus composite flame retardant, 10 to 20 parts of flexibilizer, 10 to 15 parts of filler, 8 to 18 parts of modified glass fibers, 3 to 7 parts of antioxidant and 3 to 7 parts of lubricant. The modified polypropylene plastic provided by the invention has excellent mechanical properties (tensile property, normal-temperature and low-temperature impact properties), flame retardance and water resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of modified polypropylene plastics, and in particular relates to modified polypropylene plastics added with glass fiber and a preparation method thereof. Background Art

[0002] Polypropylene is a semi-crystalline polymer with light weight, good chemical stability, and easy processing and molding. It is widely used in automobiles, home appliances, medical and other fields.

[0003] In recent years, lightweighting has been a development trend in the new energy vehicle industry. As the core power source of new energy vehicles, the battery pack is composed of a battery module wrapped in a shell. Among them, the shell is crucial to ensure the safe operation and external protection of the battery module, so the materials used are required to have corrosion resistance, insulation, resistance to normal and low temperature (-25°C) impact, and flame retardancy. The upper shell of the battery pack is the upper cover, which is mainly used to provide protection and sealing functions. Polypropylene has broad application prospects as a battery pack cover material due to its light density, corrosion resistance, low price and easy recycling.

[0004] However, polypropylene has the disadvantages of high low-temperature brittleness and poor flame retardancy and cannot meet the requirements of impact and flame retardancy of the upper cover material. Therefore, polypropylene needs to be flame-retardant and toughened.

[0005] The Chinese patent with the authorization publication number CN109181101A discloses a glass fiber reinforced flame retardant polypropylene composite material for battery pack cover and its preparation method. The composite material includes the following raw materials in parts by weight: 18.4-58.7 parts by weight of polypropylene, 20-40 parts by weight of glass fiber, 20-30 parts by weight of flame retardant, 1-10 parts by weight of interfacial compatibilizer, 0.2-0.6 parts by weight of microstructure adjustment additive, and 0.1-1 parts by weight of antioxidant. This technical solution adopts the processing method of melt pre-impregnation continuous long fiber for production, which not only meets the requirements of the material performance of the parts, but also solves the problems of difficult processing and low yield under high powder filling conditions, simplifies the original two-step processing method into one-step processing, simplifies the processing technology, improves the material yield, and reduces the manufacturing cost. However, the processing fluidity of the melt pre-impregnation continuous long fiber processing method is low, and it is not suitable for injection molding to manufacture large battery pack covers. Such large parts can only be prepared by the more expensive compression molding method.

[0006] The Chinese patent with the authorization publication number CN115160688B discloses a flame-retardant polypropylene composite material for the upper cover of the battery pack of new energy vehicles and its preparation method. The flame-retardant polypropylene composite material includes the following components in mass percentage: high melt strength polypropylene 20-60wt%, melt strength modifier 5-30wt%, thermoplastic elastomer 1-5wt%, flame retardant 20-30wt%, inorganic filler 5-15wt%; the melt strength modifier is polyethylene. This technical solution uses high melt strength polypropylene as the main matrix, which greatly improves the defect that conventional polypropylene materials are difficult to form by vacuum molding; polyethylene is used as a melt strength modifier to effectively improve the phenomenon of low melt strength of polypropylene leading to vacuum molding cracks, and improves the processing performance of the flame-retardant polypropylene composite material. However, this technical solution does not pay attention to the impact performance of the flame-retardant polypropylene composite material at low temperatures. Summary of the invention

[0007] In view of the above problems, the present invention provides a modified polypropylene plastic with added glass fiber and a preparation method thereof. The modified polypropylene plastic of the present invention has excellent mechanical properties (tensile properties, impact properties at room temperature and low temperature), flame retardancy and water resistance.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a modified polypropylene plastic with added glass fiber, wherein the raw materials include, by weight: 50-70 parts of polypropylene, 15-25 parts of modified sepiolite / nitrogen-phosphorus composite flame retardant, 10-20 parts of toughening agent, 10-15 parts of filler, 8-18 parts of modified glass fiber, 3-7 parts of antioxidant, and 3-7 parts of lubricant; The preparation method of the toughening agent comprises the following steps: S1, mixing octamethylsilsesquioxane, sodium dodecylbenzene sulfonate and water, and stirring to obtain a core layer emulsion; S2, methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, trimethylolpropane triacrylate, sodium dodecylbenzenesulfonate, potassium persulfate and water are mixed and stirred to obtain a shell emulsion; S3, mixing the core layer emulsion and the shell layer emulsion, adding potassium persulfate dropwise, and continuing to stir after the addition is complete, to obtain a core-shell emulsion A with octamethylsilsesquioxane as the core and polyacrylate as the shell; S4, butadiene, sodium dodecylbenzene sulfonate, divinylbenzene and water are uniformly mixed, potassium persulfate is added for reaction, and a polybutadiene core emulsion is obtained; the polybutadiene core emulsion, methyl methacrylate, butyl acrylate and hydroxyethyl acrylate are stirred for reaction, the temperature is lowered after the reaction is completed, 1,6-hexamethylene diisocyanate and dibutyltin dilaurate are added, and the temperature is raised for reaction, so as to obtain a core-shell emulsion B with butadiene rubber as a core, polyacrylate as a shell and isocyanate-terminated; S5. Mix the core-shell emulsion A and the core-shell emulsion B, add dibutyltin dilaurate, heat and react, and filter, wash and dry after the reaction is completed.

[0009] During the research and development process, the inventors found that when a core-shell toughening agent with octamethylsilsesquioxane as the core and polyacrylate as the shell is used, the impact performance of the modified polypropylene plastic at room temperature (23°C) can be improved, but the impact performance at low temperature (-25°C) is poor. In order to solve this technical problem, the inventors tried to add a core-shell toughening agent with polybutadiene rubber as the core and polyacrylate as the shell, and found that the impact performance at low temperature still could not be improved. The inventors creatively combined the core-shell emulsion A and the core-shell emulsion B by chemical bonds to prepare a toughening agent, so that the modified polypropylene plastic has excellent impact performance at both room temperature and low temperature. At the same time, the modified polypropylene plastic has a higher tensile strength, achieving a balance between the rigidity and toughness of the modified polypropylene plastic; the inventors speculate that this is because the toughening agent of the present invention has a multi-level structure: octamethylsilsesquioxane-polyacrylate-polyacrylate-butadiene rubber, so that when the toughening agent is dispersed in a continuous phase polypropylene system, the toughening agent can hinder the formation and diffusion of silver streaks below the glass transition temperature of polypropylene; at the same time, the polyacrylate layer allows the octamethylsilsesquioxane to produce stress concentration, and when the modified polypropylene is subjected to external force, hole absorption and consumption capabilities are formed, further hindering the formation and diffusion of silver streaks inside the polypropylene.

[0010] In some preferred embodiments, the mass ratio of octamethylsilsesquioxane, sodium dodecylbenzenesulfonate and water in step S1 is (10-20): (4-6): (50-70).

[0011] In some preferred embodiments, step S1 specifically comprises: mixing octamethylsilsesquioxane, sodium dodecylbenzenesulfonate and water, and stirring at a temperature of 60-70° C. for 3-5 hours to obtain a core layer emulsion.

[0012] In some preferred embodiments, the mass ratio of methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, trimethylolpropane triacrylate, sodium dodecylbenzenesulfonate, sodium persulfate and water in step S2 is (8-12): (10-14): (6-10): (3-7): (0.5-1.5): (0.3-0.8): (60-80).

[0013] In some preferred embodiments, step S2 specifically comprises: mixing methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, trimethylolpropane triacrylate, sodium dodecylbenzenesulfonate, potassium persulfate and water, stirring at a temperature of 80-90° C. for 3-5 h to obtain a shell emulsion.

[0014] In some preferred embodiments, the mass ratio of the core layer emulsion, the shell layer emulsion and potassium persulfate in step S3 is (10-15): (3-7): (0.1-0.3).

[0015] In some preferred embodiments, step S3 specifically comprises: mixing the core layer emulsion and the shell layer emulsion, adding potassium persulfate dropwise, and continuing stirring after the addition is complete. The stirring temperature is 100-120° C., and the stirring time is 5-7 h to obtain a core-shell emulsion A with octamethylsilsesquioxane as the core and polyacrylate as the shell.

[0016] In some preferred embodiments, the mass ratio of butadiene, sodium dodecylbenzene sulfonate, divinylbenzene, potassium persulfate and water in step S4 is (2-4): (0.3-0.5): (0.05-0.1): (0.01-0.03): (15-20).

[0017] In some preferred embodiments, the mass ratio of butadiene, methyl methacrylate, butyl acrylate and hydroxyethyl acrylate in step S4 is (20-40): (3-5): (15-35): (8-12).

[0018] In some preferred embodiments, the mass ratio of hydroxyethyl acrylate, hexamethylene diisocyanate and dibutyltin dilaurate in step S4 is (4-6): (9-14): (0.03-0.08).

[0019] In some preferred embodiments, step S4 is specifically as follows: butadiene, sodium dodecylbenzene sulfonate, divinylbenzene and water are mixed evenly, potassium persulfate is added, and the mixture is reacted at 60-70°C for 1-3h to obtain a polybutadiene core emulsion; the polybutadiene core emulsion, methyl methacrylate, butyl acrylate and hydroxyethyl acrylate are stirred, and the mixture is reacted at 60-70°C for 4-6h. After the reaction, the mixture is cooled to 25°C, 1,6-hexamethylene diisocyanate and dibutyltin dilaurate are added, the mixture is heated to 60-70°C and reacted for 0.5-1.5h to obtain an isocyanate-terminated core-shell emulsion B having a butadiene rubber core and a polyacrylate shell.

[0020] In some preferred embodiments, in step S5, the mass ratio of core-shell emulsion A, core-shell emulsion B and dibutyltin dilaurate is (1-3): (1-3): (0.02-0.04).

[0021] In some preferred embodiments, step S5 is specifically as follows: mixing the core-shell emulsion A and the core-shell emulsion B, adding dibutyltin dilaurate, heating to 60-70° C. for reaction for 1-2 hours, filtering, washing and drying after the reaction is completed.

[0022] In some preferred embodiments, the polypropylene is a mixture of copolymer polypropylene A and copolymer polypropylene B; the mass ratio of the two is (5-8):1.

[0023] In some preferred embodiments, the melt flow rate of the copolymerized polypropylene A at 230° C. and 2.16 kg is 8-15 g / 10 min; the melt flow rate of the copolymerized polypropylene B at 230° C. and 2.16 kg is 25-35 g / 10 min.

[0024] Preferably, the copolymer polypropylene A is Achieve™ Advanced PP7123KNE1.

[0025] Preferably, the copolymer polypropylene B is Achieve™ Advanced PP8285E1.

[0026] In some preferred embodiments, the preparation method of the modified sepiolite / nitrogen-phosphorus composite flame retardant comprises the following steps: dispersing sepiolite and PVP (polyvinyl pyrrolidone) in NMP (N-methylpyrrolidone), ultrasonically homogenizing for 2-3 hours, filtering, and drying to obtain the modified sepiolite; placing melamine, dimethyl methylphosphonate, DMF (N,N-dimethylformamide), and sodium hydroxide in a reactor and reacting at 130-150° C. for 3-5 hours to obtain a nitrogen-phosphorus composite flame retardant; placing the modified sepiolite in a vacuum-sealed reactor, evacuating the reactor, and sucking the nitrogen-phosphorus composite flame retardant into the reactor under the action of negative pressure, keeping the reactor in a closed state for 10-15 hours, filtering, and drying to obtain the product.

[0027] The battery pack cover material not only needs to be flame retardant, but also needs to have good water resistance. The inventors found during the research and development process that when a nitrogen-phosphorus composite flame retardant is used, the obtained modified polypropylene plastic has good flame retardant properties, but after being soaked in water, the flame retardant properties decrease significantly. In order to solve this technical problem, the inventors creatively prepared a modified sepiolite / nitrogen-phosphorus composite flame retardant. The porous structure and high specific surface area of ​​the modified sepiolite firmly adsorb the nitrogen-phosphorus composite flame retardant on the outer surface and internal micropores of the sepiolite, which not only avoids the nitrogen-phosphorus composite flame retardant in water The invention discloses a novel nanostructured carbon fiber composite flame retardant, which is a nanostructured carbon fiber composite flame retardant. The nanostructured carbon fiber composite flame retardant ...

[0028] Preferably, the ratio of the sepiolite, PVP and NMP is 0.1 g: (0.3-0.5) g: 100 mL.

[0029] Preferably, the temperature of the ultrasonic homogenization is 40-50°C, and the rotation speed is 5000-10000rpm.

[0030] Preferably, the molar ratio of melamine, dimethyl methylphosphonate, DMF and sodium hydroxide is 1:(1-3):(1.5-2):0.01.

[0031] Preferably, the mass ratio of the modified sepiolite to the nitrogen-phosphorus composite flame retardant is (4-8): (15-25).

[0032] In some preferred embodiments, the preparation method of the modified glass fiber comprises the following steps: placing short glass fibers in water, stirring the mixture at a speed of 15000-20000 rpm using a homogenizer for 15-30 min to obtain short glass fiber slurry; placing g-alumina nanofibers in a PVP aqueous solution containing potassium hydroxide, stirring the mixture at a speed of 3000-5000 rpm using a homogenizer for 15-30 min to obtain a g-alumina nanofiber dispersion; mixing the short glass fiber slurry and the g-alumina nanofiber dispersion, stirring the mixture at a speed of 3000-5000 rpm using a homogenizer for 1-2 h, and filtering the mixture.

[0033] Preferably, the ratio of the chopped glass fiber to water is (1-3):100.

[0034] Preferably, the mass ratio of the g-alumina nanofibers to the PVP aqueous solution containing potassium hydroxide is (0.1-0.3):100.

[0035] Preferably, the concentration of potassium hydroxide in the potassium hydroxide-containing PVP aqueous solution is 0.1-0.5M.

[0036] Preferably, the concentration of the PVP aqueous solution is 0.5-1 wt %.

[0037] Preferably, the mass ratio of the chopped glass fibers to the g-alumina nanofibers is (50-70):(30-50), preferably 60:40.

[0038] Preferably, the chopped glass fibers include chopped glass fibers A and chopped glass fibers B, and the mass ratio of the two is (8-12):(0.5-1.5); the monofilament diameter of the chopped glass fibers A is 10-13 μm, and the chopped length is 3-4.5 mm; the chopped glass fibers B are shaped chopped glass fibers; the shape ratio of the shaped chopped glass fibers is 2-5, the monofilament diameter is 15-17 μm, and the short side monofilament diameter is 6-9 μm.

[0039] Preferably, the chopped glass fiber A is ECS305K-3-K produced by Chongqing International Composite Materials Co., Ltd.; and the chopped glass fiber B is ECS301HP-3-M3 produced by Chongqing International Composite Materials Co., Ltd.

[0040] Preferably, the g-alumina nanofibers have a diameter of 4-8 nm and a length of 200-300 nm.

[0041] In some preferred embodiments, the mass ratio of the modified sepiolite / nitrogen-phosphorus composite flame retardant, toughening agent and modified glass fiber is (1.3-1.9):(0.9-1.3):1.

[0042] The interface compatibility between glass fiber and polypropylene matrix is ​​poor, and the interface bonding force is weak. The inventor creatively prepared short glass fibers coated with g-alumina nanofibers. When the short glass fibers include short glass fibers A and short glass fibers B, the obtained modified glass fibers act together with the toughening agent and the modified sepiolite / nitrogen-phosphorus composite flame retardant of the present invention, so that the modified polypropylene has excellent mechanical properties (tensile properties, room temperature and low temperature impact properties), flame retardancy and water resistance. The inventor speculates that this is because the surface of the short glass fibers coated with g-alumina nanofibers has a micro-nano structure, which improves the short glass fibers. The surface roughness and specific surface area of ​​the glass fiber not only have good compatibility with the polypropylene in the polypropylene system, but also work together with the toughening agent and the modified sepiolite / nitrogen-phosphorus composite flame retardant to form multiple gradient interfaces between the interfaces of the polypropylene system, thereby improving the mechanical properties, flame retardancy and water resistance of the modified polypropylene; at the same time, the inventors also found that when the mass ratio of the modified sepiolite / nitrogen-phosphorus composite flame retardant, the toughening agent and the modified glass fiber is not in the range of (1.3-1.9): (0.9-1.3): 1, the mechanical properties, flame retardancy and water resistance of the modified polypropylene decrease.

[0043] In some preferred embodiments, the filler is selected from at least one of talc, calcium carbonate, and wollastonite, preferably talc.

[0044] In some preferred embodiments, the antioxidant is selected from at least one of antioxidant 1010 (pentaerythritol tetrakis[methyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and antioxidant 168 (tris(2,4-di-tert-butyl)phenyl phosphite), preferably antioxidant 1010.

[0045] In some preferred embodiments, the lubricant is selected from at least one of zinc stearate, calcium stearate, polyethylene wax, and polypropylene wax, preferably zinc stearate.

[0046] The second aspect of the present invention provides a method for preparing the above-mentioned modified polypropylene plastic with added glass fiber, comprising the following steps: polypropylene, modified sepiolite / nitrogen-phosphorus composite flame retardant, toughening agent, filler, modified glass fiber, antioxidant, and lubricant are stirred and mixed uniformly to obtain a mixture; the mixture is melted and extruded using a twin-screw extruder to obtain.

[0047] In some preferred embodiments, the screw speed of the twin-screw extruder is 200-400 rpm, and the melting temperature is 180-200°C.

[0048] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention creatively combines core-shell emulsion A and core-shell emulsion B by chemical bonds to prepare a toughening agent, so that the modified polypropylene plastic has excellent impact properties at both room temperature and low temperature. At the same time, the modified polypropylene plastic has a higher tensile strength, achieving a balance between the rigidity and toughness of the modified polypropylene plastic.

[0049] 2. The present invention creatively prepares a modified sepiolite / nitrogen-phosphorus composite flame retardant. The porous structure and high specific surface area of ​​the modified sepiolite firmly adsorb the nitrogen-phosphorus composite flame retardant on the outer surface and internal micropores of the sepiolite, which not only prevents the nitrogen-phosphorus composite flame retardant from falling off in water, but also the sepiolite can effectively increase the formation of the carbon layer and the amount of carbon produced during the combustion of polypropylene, thereby improving the flame retardant properties of the modified polypropylene. At the same time, the addition of the modified sepiolite / nitrogen-phosphorus composite flame retardant avoids the decrease in the tensile properties and impact properties of the modified polypropylene plastic.

[0050] 3. The present invention creatively prepares short glass fibers coated with g-alumina nanofibers. When the short glass fibers include short glass fibers A and short glass fibers B, the obtained modified glass fibers work together with the toughening agent and the modified sepiolite / nitrogen-phosphorus composite flame retardant of the present invention, so that the modified polypropylene has excellent mechanical properties (tensile properties, room temperature and low temperature impact properties), flame retardancy and water resistance. When the mass ratio of the modified sepiolite / nitrogen-phosphorus composite flame retardant, the toughening agent and the modified glass fibers is controlled to be (1.3-1.9): (0.9-1.3): 1, the mechanical properties, flame retardancy and water resistance of the modified polypropylene are avoided from decreasing. DETAILED DESCRIPTION

[0051] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.

[0052] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0053] In the following examples and comparative examples, unless otherwise specified, all raw materials used were commercially available or prepared by conventional methods in the art.

[0054] Example 1

[0055] A modified polypropylene plastic with added glass fiber, the raw materials of which include, by weight: 50 parts of polypropylene, 15 parts of modified sepiolite / nitrogen-phosphorus composite flame retardant, 10 parts of toughening agent, 10 parts of filler, 8 parts of modified glass fiber, 3 parts of antioxidant, and 3 parts of lubricant; The polypropylene is a mixture of copolymer polypropylene A and copolymer polypropylene B; the mass ratio of the two is 6:1; the copolymer polypropylene A is Achieve™ Advanced PP7123KNE1, and the melt flow rate at 230°C and 2.16kg is 11g / 10min; the copolymer polypropylene B is Achieve™ Advanced PP8285E1, and the melt flow rate at 230°C and 2.16kg is 30g / 10min.

[0056] The preparation method of the modified sepiolite / nitrogen-phosphorus composite flame retardant comprises the following steps: dispersing sepiolite (purchased from Hebei Hongli Sepiolite Wool Co., Ltd.) and PVP (purchased from Shenggong Biotechnology (Shanghai) Co., Ltd., MW 40,000) in NMP (CAS No.: 872-50-4), ultrasonically homogenizing for 2.5 hours, filtering, and drying to obtain modified sepiolite; the ratio of the sepiolite, PVP, and NMP is 0.1 g: 0.4 g: 100 mL; the temperature of the ultrasonic homogenization is 45° C., and the rotation speed is 8000 rpm; Melamine (CAS No.: 108-78-1), dimethyl methylphosphonate (CAS 756-79-6), DMF (CAS No.: 68-12-2) and sodium hydroxide are placed in a reactor and reacted at 140° C. for 4 hours to obtain a nitrogen-phosphorus composite flame retardant; the molar ratio of melamine, dimethyl methylphosphonate, DMF and sodium hydroxide is 1:2:1.8:0.01; The modified sepiolite is placed in a vacuum-sealed reactor, the reactor is evacuated, the nitrogen-phosphorus composite flame retardant is sucked into the reactor under the action of negative pressure, the reactor is kept in a closed state for 12 hours, filtered, and dried to obtain the product; the mass ratio of the modified sepiolite to the nitrogen-phosphorus composite flame retardant is 6:20.

[0057] The preparation method of the toughening agent comprises the following steps: S1. Mix octamethylsilsesquioxane (CAS No.: 17865-85-9), sodium dodecylbenzene sulfonate (CAS No.: 25155-30-0) and water, and stir at a temperature of 65°C for 4 hours to obtain a core layer emulsion; the mass ratio of octamethylsilsesquioxane, sodium dodecylbenzene sulfonate and water is 15:5:60; S2. Mix methyl methacrylate (CAS No.: 80-62-6), butyl acrylate (CAS No.: 141-32-2), hydroxyethyl acrylate (CAS No.: 818-61-1), trimethylolpropane triacrylate (CAS No.: 15625-89-5), sodium dodecylbenzenesulfonate, potassium persulfate (CAS No.: 7727-21-1) and water, and stir at a temperature of 85°C for 4 hours to obtain a shell emulsion; the mass ratio of methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, trimethylolpropane triacrylate, sodium dodecylbenzenesulfonate, sodium persulfate and water is 10:12:8:5:1:0.5:70; S3, mixing the core layer emulsion and the shell layer emulsion, adding potassium persulfate dropwise, and continuing stirring after the addition is complete, the stirring temperature is 110°C, and the stirring time is 6 hours to obtain a core-shell emulsion A with octamethylsilsesquioxane as the core and polyacrylate as the shell; the mass ratio of the core layer emulsion, the shell layer emulsion and potassium persulfate is 12:5:0.2; S4. Evenly mix butadiene (CAS No.: 106-99-0), sodium dodecylbenzene sulfonate, divinylbenzene (CAS No.: 1321-74-0) and water, add potassium persulfate, and react at 65°C for 2h to obtain a polybutadiene core emulsion; the mass ratio of butadiene, sodium dodecylbenzene sulfonate, divinylbenzene, potassium persulfate and water is 3:0.4:0.08:0.02:18; The polybutadiene core emulsion, methyl methacrylate, butyl acrylate and hydroxyethyl acrylate were stirred and reacted at 65°C for 5 hours. After the reaction, the temperature was lowered to 25°C, 1,6-hexamethylene diisocyanate (CAS No.: 822-06-0) and dibutyltin dilaurate (CAS No.: 77-58-7) were added, and the temperature was raised to 65°C for reaction for 1 hour to obtain an isocyanate-terminated core-shell emulsion B with butadiene rubber as the core and polyacrylate as the shell; the mass ratio of butadiene, methyl methacrylate, butyl acrylate and hydroxyethyl acrylate was 30:4:25:10; the mass ratio of hydroxyethyl acrylate, 1,6-hexamethylene diisocyanate and dibutyltin dilaurate was 5:12:0.05; S5. Mix core-shell emulsion A and core-shell emulsion B, add dibutyltin dilaurate, heat to 65°C and react for 1.5 hours. After the reaction, filter, wash and dry to obtain the product; the mass ratio of core-shell emulsion A, core-shell emulsion B and dibutyltin dilaurate is 2:2:0.03.

[0058] The preparation method of the modified glass fiber comprises the following steps: placing short glass fibers in water (the ratio of short glass fibers to water is 2:100), using a homogenizer to stir at a rotation speed of 18000 rpm for 25 minutes to obtain short glass fiber slurry; placing g-alumina nanofibers in a PVP aqueous solution containing potassium hydroxide (with a concentration of 0.8 wt%), using a homogenizer to stir at a rotation speed of 4000 rpm for 25 minutes to obtain a g-alumina nanofiber dispersion; mixing the short glass fiber slurry and the g-alumina nanofiber dispersion, using a homogenizer to stir at a rotation speed of 4000 rpm for 1.5 hours, and filtering to obtain the modified glass fiber.

[0059] The mass ratio of the g-alumina nanofibers to the PVP aqueous solution containing potassium hydroxide is 0.2:100.

[0060] The concentration of potassium hydroxide in the potassium hydroxide-containing PVP aqueous solution is 0.3M.

[0061] The mass ratio of the chopped glass fibers to the g-alumina nanofibers is 60:40.

[0062] The chopped glass fibers include chopped glass fibers A and chopped glass fibers B, and the mass ratio of the chopped glass fibers A and B is 10:1; The chopped glass fiber A is ECS305K-3-K produced by Chongqing International Composite Materials Co., Ltd., with a single filament diameter of 10-13 μm and a chopped length of 3-4.5 mm; The chopped glass fibers are shaped chopped glass fibers; the chopped glass fibers B are ECS301HP-3-M3 produced by Chongqing International Composite Materials Co., Ltd., with a shape ratio of 2-5, a single fiber diameter of 15-17 μm, and a short-side single fiber diameter of 6-9 μm.

[0063] The g-alumina nanofibers have a diameter of 4-8 nm and a length of 200-300 nm, and were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., item number: 100694, serial number: XFJ52.

[0064] The filler is talcum powder, purchased from Qingdao Kaiwell Powder Engineering Technology Co., Ltd., plastic grade.

[0065] The antioxidant is antioxidant 1010 (CAS No.: 6683-19-8).

[0066] The lubricant is zinc stearate (CAS No.: 557-05-1).

[0067] The preparation method of the modified polypropylene plastic with added glass fiber comprises the following steps: polypropylene, modified sepiolite / nitrogen-phosphorus composite flame retardant, toughening agent, filler, modified glass fiber, antioxidant and lubricant are stirred and mixed uniformly to obtain a mixture; the mixture is melted and extruded using a twin-screw extruder to obtain the mixture.

[0068] The screw speed of the twin-screw extruder is 300 rpm, and the melting temperature is 190°C.

[0069] Example 2

[0070] The difference from Example 1 is that the modified polypropylene plastic with added glass fiber, calculated by mass, includes the following raw materials: 70 parts of polypropylene, 25 parts of modified sepiolite / nitrogen-phosphorus composite flame retardant, 20 parts of toughening agent, 15 parts of filler, 18 parts of modified glass fiber, 7 parts of antioxidant, and 7 parts of lubricant; the rest are the same.

[0071] The preparation method of the modified polypropylene plastic with added glass fiber is the same as that in Example 1.

[0072] Example 3

[0073] The difference from Example 1 is that the modified polypropylene plastic with added glass fiber, calculated by mass, includes the following raw materials: 60 parts of polypropylene, 20 parts of modified sepiolite / nitrogen-phosphorus composite flame retardant, 15 parts of toughening agent, 12 parts of filler, 14 parts of modified glass fiber, 5 parts of antioxidant, and 5 parts of lubricant; the rest are the same.

[0074] The preparation method of the modified polypropylene plastic with added glass fiber is the same as that in Example 1.

[0075] Comparative Example 1 The difference from Example 3 is that the preparation method of the toughening agent comprises the following steps: S1, mixing octamethylsilsesquioxane, sodium dodecylbenzene sulfonate and water, and stirring to obtain a core layer emulsion; S2, methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, trimethylolpropane triacrylate, sodium dodecylbenzenesulfonate, potassium persulfate and water are mixed and stirred to obtain a shell emulsion; S3, mixing the core layer emulsion and the shell layer emulsion, adding potassium persulfate dropwise, and continuing stirring after the addition is complete to obtain a core-shell emulsion A with octamethylsilsesquioxane as the core and polyacrylate as the shell, adding a 10% by mass fraction of calcium chloride solution (the mass ratio of the calcium chloride solution to the core-shell emulsion A is 1:1) to break the emulsion, filtering, drying, and washing after breaking the emulsion to obtain a toughening agent A; S4, butadiene, sodium dodecylbenzene sulfonate, divinylbenzene and water are mixed evenly, potassium persulfate is added for reaction, and a polybutadiene core emulsion is obtained; the polybutadiene core emulsion, methyl methacrylate, butyl acrylate and hydroxyethyl acrylate are stirred for reaction, the temperature is lowered after the reaction is completed, 1,6-hexamethylene diisocyanate and dibutyltin dilaurate are added, the temperature is raised for reaction, and an isocyanate-terminated core-shell emulsion B with butadiene rubber as the core and polyacrylate as the shell is obtained, and a 10% by mass calcium chloride solution (the mass ratio of the calcium chloride solution to the core-shell emulsion B is 1:1) is added for demulsification, and after demulsification, the toughening agent B is obtained by filtering, drying and washing; S5. Mix toughening agent A and toughening agent B; the rest are the same.

[0076] Comparative Example 2 The difference from Example 3 is that the modified sepiolite / nitrogen-phosphorus composite flame retardant is replaced with a nitrogen-phosphorus composite flame retardant of the same mass, and the rest are the same.

[0077] Comparative Example 3 The difference from Example 3 is that the modified sepiolite / nitrogen-phosphorus composite flame retardant is replaced by modified sepiolite of equal mass, and the rest are the same.

[0078] Comparative Example 4 The difference from Example 3 is that the g-alumina nanofibers are replaced with polyimide nano short fibers of equal mass and ordinary specifications purchased from Jiangxi Xiancai Nanofiber Technology Co., Ltd.; the rest are the same.

[0079] Comparative Example 5 The difference from Example 3 is that the chopped glass fiber B is replaced by chopped glass fiber A of the same mass, and the rest is the same.

[0080] Comparative Example 6 The difference from Example 3 is that the modified polypropylene plastic with added glass fiber includes, by mass, 60 parts of polypropylene, 23 parts of modified sepiolite / nitrogen-phosphorus composite flame retardant, 16 parts of toughening agent, 12 parts of filler, 10 parts of modified glass fiber, 5 parts of antioxidant, and 5 parts of lubricant; the rest are the same.

[0081] Performance Test: The performance tests were conducted on the modified polypropylene plastics with added glass fibers in Examples 1-3 and Comparative Examples 1-6: 1. Tensile strength: Test standard: GB / T 1040.2-2022; 2. Izod notched impact strength (23°C and -25°C): Test standard: GB / T 1843-2008; 3. Flame retardancy: Test standard: UL94; 4. Water resistance: The modified polypropylene plastics with added glass fiber of Examples 1-3 and Comparative Examples 1-6 were placed in a 70°C constant temperature water bath, taken out after 168 hours, dried at 120°C for 3 hours, and tested for flame retardancy after cooling to 25°C. The results are shown in Table 1: Table 1 Performance test results of modified polypropylene plastics with added glass fiber in Examples 1-3 and Comparative Examples 1-6 Tensile strength (MPa) <![CDATA[Izod impact strength at 23°C (KJ / m 2 )]]> <![CDATA[Izod impact strength of cantilever beam / -25 °C (kJ / m 2 )]]> Flame retardant (2.5mm) Water resistance (2.5mm) Example 1 50.1 31.4 19.2 V0 V0 Example 2 46.1 34.9 22.5 V0 V0 Example 3 48.5 36.6 24.1 V0 V0 Comparative Example 1 43.6 35.9 13.7 V0 V0 Comparative Example 2 39.5 28.6 15.9 V1 V2 Comparative Example 3 42.1 31.3 17.4 V2 V2 Comparative Example 4 34.2 23.5 15.1 V0 V1 Comparative Example 5 36.6 25.8 16.5 V0 V0 Comparative Example 6 38.7 28.3 16.9 V1 V2 It can be seen from Table 1 that the modified polypropylene plastics with added glass fibers of Examples 1-3 have higher tensile strength, room temperature and low temperature Izod notched impact strength, flame retardancy and water resistance; Comparative Example 1 is to directly mix a core-shell toughening agent with octamethylsilsesquioxane as a core and polyacrylate as a shell and a core-shell toughening agent with butadiene rubber as a core and polyacrylate as a shell; it is not possible to improve the low-temperature impact performance of the modified polypropylene plastic with added glass fiber; Comparative Example 2 is to replace the modified sepiolite / nitrogen-phosphorus composite flame retardant with an equal mass of nitrogen-phosphorus composite flame retardant; Comparative Example 3 is to replace the modified sepiolite / nitrogen-phosphorus composite flame retardant with an equal mass of modified sepiolite; the flame retardant properties and water resistance of the obtained modified polypropylene plastic with added glass fiber are significantly reduced, and the mechanical properties are also reduced; In comparative example 4, the g-alumina nanofibers are replaced with polyimide nanofibers of equal mass; in comparative example 5, the chopped glass fiber B is replaced with chopped glass fiber A of equal mass; the mechanical properties of the modified polypropylene plastic with added glass fiber are significantly reduced; at the same time, the water resistance of comparative example 4 is reduced; In Comparative Example 6, the mass ratio of the modified sepiolite / nitrogen-phosphorus composite flame retardant, toughening agent and modified glass fiber is not in the range of (1.3-1.9):(0.9-1.3):1, and the mechanical properties, flame retardancy and water resistance of the obtained modified polypropylene plastic with added glass fiber are all reduced.

[0082] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A modified polypropylene plastic with added glass fiber, characterized in that: The raw materials include, by weight: 50-70 parts of polypropylene, 15-25 parts of modified sepiolite / nitrogen-phosphorus composite flame retardant, 10-20 parts of toughening agent, 10-15 parts of filler, 8-18 parts of modified glass fiber, 3-7 parts of antioxidant, and 3-7 parts of lubricant; The preparation method of the toughening agent comprises the following steps: S1, mixing octamethylsilsesquioxane, sodium dodecylbenzene sulfonate and water, and stirring to obtain a core layer emulsion; S2, methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, trimethylolpropane triacrylate, sodium dodecylbenzenesulfonate, potassium persulfate and water are mixed and stirred to obtain a shell emulsion; S3, mixing the core layer emulsion and the shell layer emulsion, adding potassium persulfate dropwise, and continuing to stir after the addition is complete, to obtain a core-shell emulsion A with octamethylsilsesquioxane as the core and polyacrylate as the shell; S4, butadiene, sodium dodecylbenzene sulfonate, divinylbenzene and water are uniformly mixed, potassium persulfate is added for reaction, and a polybutadiene core emulsion is obtained; the polybutadiene core emulsion, methyl methacrylate, butyl acrylate and hydroxyethyl acrylate are stirred for reaction, the temperature is lowered after the reaction is completed, 1,6-hexamethylene diisocyanate and dibutyltin dilaurate are added, and the temperature is raised for reaction, so as to obtain a core-shell emulsion B with butadiene rubber as a core, polyacrylate as a shell and isocyanate-terminated; S5. Mix the core-shell emulsion A and the core-shell emulsion B, add dibutyltin dilaurate, heat and react, and filter, wash and dry after the reaction is completed.

2. The modified polypropylene plastic with added glass fiber according to claim 1, characterized in that: The polypropylene is a mixture of copolymer polypropylene A and copolymer polypropylene B; the mass ratio of the two is (5-8):1; The copolymerized polypropylene A has a melt flow rate of 8-15 g / 10 min at 230° C. and 2.16 kg; The copolymerized polypropylene B has a melt flow rate of 25-35 g / 10 min at 230° C. and 2.16 kg.

3. The modified polypropylene plastic with added glass fiber according to claim 2, characterized in that: The preparation method of the modified sepiolite / nitrogen-phosphorus composite flame retardant comprises the following steps: dispersing sepiolite and PVP in NMP, ultrasonically homogenizing for 2-3 hours, filtering, and drying to obtain the modified sepiolite; placing melamine, dimethyl methylphosphonate, DMF, and sodium hydroxide in a reactor and reacting at 130-150° C. for 3-5 hours to obtain the nitrogen-phosphorus composite flame retardant; placing the modified sepiolite in a vacuum-sealed reactor, evacuating the reactor, sucking the nitrogen-phosphorus composite flame retardant into the reactor under the action of negative pressure, keeping the reactor in a closed state and standing for 10-15 hours, filtering, and drying to obtain the modified sepiolite.

4. The modified polypropylene plastic with added glass fiber according to claim 3, characterized in that: The mass ratio of the modified sepiolite to the nitrogen-phosphorus composite flame retardant is (4-8): (15-25).

5. The modified polypropylene plastic with added glass fiber according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises the following steps: placing short glass fibers in water, stirring the mixture at a rotation speed of 15000-20000 rpm by using a homogenizer for 15-30 minutes to obtain short glass fiber slurry; placing g-alumina nanofibers in a PVP aqueous solution containing potassium hydroxide, stirring the mixture at a rotation speed of 3000-5000 rpm by using a homogenizer for 15-30 minutes to obtain a g-alumina nanofiber dispersion; mixing the short glass fiber slurry and the g-alumina nanofiber dispersion, stirring the mixture at a rotation speed of 3000-5000 rpm by using a homogenizer for 1-2 hours, and filtering the mixture to obtain the modified glass fiber.

6. The modified polypropylene plastic with added glass fiber according to claim 5, characterized in that: The chopped glass fibers include chopped glass fibers A and chopped glass fibers B, and the mass ratio of the chopped glass fibers A and B is (8-12): (0.5-1.5).

7. The modified polypropylene plastic with added glass fiber according to claim 6, characterized in that: The chopped glass fibers A have a monofilament diameter of 10-13 μm and a chopped length of 3-4.5 mm.

8. The modified polypropylene plastic with added glass fiber according to claim 7, characterized in that: The chopped glass fibers B are shaped chopped glass fibers; the shaped chopped glass fibers have a shape ratio of 2-5, a single fiber diameter of 15-17 μm, and a short-side single fiber diameter of 6-9 μm.

9. The modified polypropylene plastic with added glass fiber according to claim 8, characterized in that: The mass ratio of the modified sepiolite / nitrogen-phosphorus composite flame retardant, toughening agent and modified glass fiber is (1.3-1.9):(0.9-1.3):

1.

10. The method for preparing the modified polypropylene plastic with added glass fiber according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing polypropylene, modified sepiolite / nitrogen-phosphorus composite flame retardant, toughening agent, filler, modified glass fiber, antioxidant and lubricant uniformly to obtain a mixture; and melting and extruding the mixture using a twin-screw extruder to obtain the mixture.

Citation Information

Patent Citations

  • Glass fiber enhanced flame retardant polypropylene composite material for upper cover of battery pack and preparation method thereof

    CN109181101A

  • A flame-retardant polypropylene composite material for new energy vehicle battery pack cover and preparation method thereof

    CN115160688B